Automated red blood cell exchange for acute drug removal in a patient with sirolimus toxicity. Issue 6 (24th January 2015) - Galera, Pallavi; Martin, Hannah C.; Welch, Linda; Sulmasy, Paula; Cerny, Jan; Greene, Mindy; Vauthrin, Michelle; Bailey, Jeffrey A.; Weinstein, Robert
Abstract : Sirolimus is an immunosuppressant used to prevent graft versus host disease in allogeneic hematopoietic stem cell transplant recipients. It has a large volume of distribution (12 ± 7.5 l/kg) and within the intravascular space ∼95% of it is bound to red blood cells. Because of potential toxic effects at high trough levels, therapeutic drug monitoring is recommended for sirolimus. We present a case of severe hepatic dysfunction due to Hepatitis B and sirolimus toxicity, in a 51‐year‐old male stem cell transplant recipient. An automated red cell exchange decreased his blood sirolimus level from 22.6 to 10.3 ng/ml (55% reduction) and improved his liver enzymes. Re‐equilibration of sirolimus from other compartments to the blood necessitated a series of four red cell exchanges, after which the sirolimus level was 4.7 ng/ml. Although the patient ultimately succumbed to multiorgan failure, red cell exchange may be considered for acute removal of sirolimus in selected patients. J. Clin. Apheresis 30:367–370, 2015. © 2015 Wiley Periodicals, Inc.